THE IMPLEMENTATION OF A LOVE-BASED CURRICULUM THROUGH SOCIAL ACTIVITIES AT PESANTREN NURULHUDA PAKANDANGAN - Mo’tasim Mo’tasim; Ellya Verawati; Amar Ma’ruf; Imam Tazali; Yukholis Yukholis; Imam Wahyudi (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to analyze the implementation of a love-based curriculum through social activities and community service at Pesantren Nurulhuda Pakandangan. The main focus of this research is on students’ involvement in various activities such as social service, community da‘wah, and humanitarian programs as a means of fostering character grounded in compassion (mahabbah). The method employed is a qualitative approach with a case study design, utilizing observation, interviews, and documentation. The findings reveal that students’ active participation in social activities is effective in developing empathy, social awareness, and sensitivity toward societal realities. Furthermore, direct field experiences strengthen the internalization of inclusive and humanistic Islamic values. Therefore, social activities and community service function not merely as external practices, but also as an effective medium for character education in shaping students who are morally grounded, responsive, and oriented toward social welfare. This study underscores that the integration of a love-based curriculum through community engagement plays a strategic role in nurturing a generation that is not only religious but also possesses a strong sense of social responsibility.